Macronutrient management for the cultivation of Soybean (Glycine max L.): A review. Issue 1 (June 2021) - Saranraj, P; Sivasakthivelan, P; Al-Tawaha, A R M; Bright, R; Imran; Amanullah; Al-Tawaha, A R; Thangadurai, D; Sangeetha, J; Rauf, A; Khalid, S; Al Sultan, W; et al.
Abstract: The review is focused on management of macronutrients for cultivating Soybean. Soybean is an important crop in the world because the only reliable plant-based source of complete protein, comparable to meat and eggs, is from soya protein. Soybean yield is crucial for meeting protein malnutrition and edible oil needs.. The wide variation in Rhizobial cell counts and nodule mass in beans are likely related to variation is Physico-chemical conditions of the soil.